1998
DOI: 10.1016/s0002-9440(10)65623-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Herpesvirus-6 Antigens in Benign and Malignant Lymphoproliferative Diseases

Abstract: Immunohistochemistry was used to look for the expression of human herpesvirus-6 (HHV-6) antigens in a well characterized series of benign , atypical, and malignant lymphoid lesions , which tested positive for the presence of HHV-6 DNA. A panel of specific antibodies against HHV-6 antigens , characteristic either of the early (p41) or late (p101K , gp106, and gp116) phases of the viral cycle , was applied to the lymphoid tissues from 15 non-Hodgkin's lymphomas , 14 Hodgkin's disease cases , 5 angioimmunoblastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 42 publications
4
110
0
3
Order By: Relevance
“…41 Disseminated infection may be associated with hepatitis, pneumonia, marrow suppression, and encephalitis. HHV-6 has also been detected, albeit at low levels, in Hodgkin's lymphoma and angioimmunoblastic lymphadenopathy, 42 and has been implicated in multiple sclerosis. 43 HHV-6 infection is common in early childhood, when it presents as a febrile illness with rash, known as roseola.…”
Section: Discussionmentioning
confidence: 99%
“…41 Disseminated infection may be associated with hepatitis, pneumonia, marrow suppression, and encephalitis. HHV-6 has also been detected, albeit at low levels, in Hodgkin's lymphoma and angioimmunoblastic lymphadenopathy, 42 and has been implicated in multiple sclerosis. 43 HHV-6 infection is common in early childhood, when it presents as a febrile illness with rash, known as roseola.…”
Section: Discussionmentioning
confidence: 99%
“…IgG antibody for Epstein-Barr virus (EBV)-viral capsid antigen and EBV-nuclear antigen, and IgM antibody for HHV-6 were negative and IgG antibody for HHV-6 was positive in the present case. In addition, HHV-6-specific DNA was detected within the histiocytes from RDD patients in 7 out of 9 cases by in situ DNA hybridization (Luppi et al 1998). The current patient had a previous infection of HHV-6.…”
Section: Clinical Reportmentioning
confidence: 99%
“…10 Initially, the atypical cytological features of the virally infected cells raised the possibility of involvement by non-Hodgkin's lymphoma with immunoblastic features. However, the lack of an aberrant phenotype and absence of evidence of a clonal T-cell process did not support this diagnosis.…”
Section: Hhv-6 In Acute Lymphadenitis I Maric Et Almentioning
confidence: 99%
“…Immunohistochemical studies 10 showed that HHV-6-positive cells in cases of reactive lymphadenopathy are plasma cells, histiocytes, and rare granulocytes. In vitro studies have shown that HHV-6 replicates and induces cytopathic effects in CD4 þ -positive T lymphocytes, but it has been also shown to be tropic for other cells including CD8…”
mentioning
confidence: 99%